Effects of tactical periodization on workload, physical fitness, and well-being in professional rugby union players during a preseason period - Hu, X.; Boisbluche, S.; Philippe, K.; Maurelli, O.; Li, S.; Xu, B.; Prioux, J. (The Journal of Strength and Conditioning Research, 2024)
Tactical periodization (TP) emerged approximately 30 years ago and has recently gained considerable attention in rugby union (RU). It aims to develop specific physical fitness components with 3 acquisition days (strength, endurance, and speed). However, no study has investigated the effects of TP on workload, physical fitness, and well-being across an RU preseason. This study aimed to determine how RU players' workload response to TP focusing on positional differences, observe the influence of a TP preseason training program on aerobic fitness and neuromuscular performance between positions, and analyze the variation of well-being reported by forwards and backs from the 3 acquisition days. Thirty-two male players completed a 6-week TP protocol. External and internal workload variables were recorded through global positioning systems and session rating of perceived exertion (s-RPE) separately. Fitness assessments included Bronco and countermovement jump (CMJ) tests. The sum of well-being indices was measured using the Hooper index. Kruskal-Wallis H tests revealed that the highest values of PlayerLoad slow, PlayerLoad slow percentage, and s-RPE were found on endurance day and the lowest on speed day. Mann-Whitney U tests showed that 15 external workload parameters were higher in backs than forwards for each acquisition day. Small improvements were observed on the Bronco test. No differences were observed in CMJ performance during the preseason period and well-being values between acquisition days. This study provides unique insights into external and internal workload variables during each acquisition day. Furthermore, it highlights TP as an efficient theoretical concept to use in an RU context.